Regulatory focus and generalized trust: the impact of prevention-focused self-regulation on trusting others - Keller, Johannes; Mayo, Ruth; Greifeneder, Rainer; Pfattheicher, Stefan (Frontiers in Psychology, 2015)
The current research suggests that taking self-regulatory mechanisms into account provides insights regarding individuals’ responses to threats in social interactions. In general, based on the notion that a prevention-focused orientation of self-regulation is associated with a need for security and a vigilant tendency to avoid losses and other types of negative events we advocate that a prevention-focused orientation, both as a disposition as well as a situationally induced state, lowers generalized trust, thus hindering cooperation within social interactions that entail threats. Specifically, we found that the more individuals’ habitual self-regulatory orientation is dominated by a prevention focus, the less likely they are to score high on a self-report measure of generalized trust (Study 1), and to express trust in a trust game paradigm as manifested in lower sums of transferred money (Studies 2 and 3). Similar findings were found when prevention focus was situationally manipulated (Study 4). Finally, one possible factor underlying the impact of prevention-focused self-regulation on generalized trust was demonstrated as individuals with a special sensitivity to negative information were significantly affected by a subtle prevention focus manipulation (vs. control condition) in that they reacted with reduced trust in the trust game (Study 5). In sum, the current findings document the crucial relevance of self-regulatory orientations as conceptualized in regulatory focus theory regarding generalized trust and responses to threats within a social interaction. The theoretical and applied implications of the findings are discussed.